Studying Factors Influencing Intention to Use Hybrid Education: A Case Study of Visual Communication Design Major Students at Chengdu Vocational University of Art - Xia, ZaiXi; Lu, Leehsing (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: Hybrid teaching follows the reform trend of China's vigorous development of online education and hybrid education. The Chengdu Vocational University of Art is the earliest art vocational university in China, and the visual communication major is the advantageous major of the university. The program of this major adopts a hybrid education model combining MOOC online courses and offline education. This study uses TAM, ASCI, UTAUT, and ECM theories to construct a model to analyze the factors affecting the hybrid education learning satisfaction of visual communication students, whose variables include virtual classroom quality, instructor characteristics, student expectations, course design quality, and course content quality. Materials and Methods: A purposive sampling method was used to distribute questionnaires to 571 students. Confirmatory factor analysis (CFA) and Structural Equation Modeling (SEM) were used to analyze the reliability, validity, goodness of fit, and hypothesis testing of the model. Results: Student satisfaction was found to greatly influence intention to use through the study. In addition, instructor characteristics and classroom quality had a supportive relationship on perceived usefulness, student expectations, course content, and perceived usefulness had a supportive relationship on satisfaction, while course design quality had no significant effect on satisfaction. Conclusion: School management and teaching teams should pay attention to the key influences on the intention of hybrid education and design programs based on research findings to help students understand the effectiveness of hybrid education and improve the quality of education.